The role of focal adhesion anchoring domains of CAS in mechanotransduction - Braniš, Jaroslav; Pataki, Csilla; Spörrer, Marina; Gerum, Richard C; Mainka, Astrid; Cermak, Vladimir; Goldmann, Wolfgang H; Fabry, Ben; Brabek, Jan; Rosel, Daniel (Scientific reports, 2017)
CAS is a docking protein, which was shown to act as a mechanosensor in focal adhesions. The unique assembly of structural domains in CAS is important for its function as a mechanosensor. The tension within focal adhesions is transmitted to a stretchable substrate domain of CAS by focal adhesion-targeting of SH3 and CCH domain of CAS, which anchor the CAS protein in focal adhesions. Mechanistic models of the stretching biosensor propose equal roles for both anchoring domains. Using deletion mutants and domain replacements, we have analyzed the relative importance of the focal adhesion anchoring domains on CAS localization and dynamics in focal adhesions as well as on CAS-mediated mechanotransduction. We confirmed the predicted prerequisite of the focal adhesion targeting for CAS-dependent mechanosensing and unraveled the critical importance of CAS SH3 domain in mechanosensing. We further show that CAS localizes to the force transduction layer of focal adhesions and that mechanical stress stabilizes CAS in focal adhesions.
Keywords: Animals; Green Fluorescent Proteins; stabilita proteinů; Fibroblasts; Recombinant Fusion Proteins; buněčná adheze; Structure-Activity Relationship; Protein Stability; proteinové domény; rekombinantní fúzní proteiny; Mice; Cell Adhesion; signální transdukce; substrátový protein asociovaný s Crk; buněčný převod mechanických signálů; fibroblasty; Protein Domains; myši; Signal Transduction; mechanický stres; zelené fluorescenční proteiny; Stress, Mechanical; Mutant Proteins; Mechanotransduction, Cellular; mutantní proteiny; vztahy mezi strukturou a aktivitou; fokální adheze; zvířata; Crk-Associated Substrate Protein; Focal Adhesions